A MEDIA EDUKASI TENTANG KADAR GULA DARAH PADA LANSIA DI SURABAYA - Agustin, Putri Agustin (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2023)
GDA (Blood sugar), or monosaccharide, is the body's main metabolic that produces energy in the form of ATP (Adenosia triphosphate). Exercise gives it enough energy to produce glucose into ATP (Adenosia triphosphate). This study used the elderly group as the research target. The purpose of this study is to identify how to reduce GDA (blood sugar) levels in the elderly in the Surabaya area and to educate elderly people to pay more attention to their blood sugar so that they can avoid blood sugar disease. The method used in this research is a descriptive qualitative method. The data collection and processing technique applied during the research was the deep interview technique. The research sample was taken from a total of 30 elderly people who were interviewed about blood sugar levels. It is known that the behavior of respondents in the knowledge of GDA (blood sugar) can be classified at a fairly good level. The results showed that out of 30 elderly people (100%) showed an increase in knowledge after the delivery of material which initially 10% increased to 90%. From the results of the discussion, it can be concluded that the implementation of sugar level education with its application is in accordance with the objectives. Researchers hope that the results of the study can be developed so that they are useful and feasible to use.